Pengaruh Belanja Modal, dan Indeks Pembangunan Manusia,Terhadap Pertumbuhan Ekonomi di Indonesia - Muhammad Fadhel Alfayed; Puti Andiny; Yani Rizal; Safuridar Safuridar (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to analyze the effect of capital expenditure and Human Development Index (HDI) on economic growth in Indonesia. Using time series data from 2011 to 2023 sourced from Indonesia's Central Bureau of Statistics (BPS), this study applies the multiple linear regression method using the Eviews 10 program. The results show that capital expenditure has a positive and significant influence on economic growth, while HDI has a positive but insignificant influence. Simultaneously, these two variables contribute significantly to economic growth with an R-squared value of 60.14%. This study emphasizes the importance of efficient capital expenditure management and efforts to improve the quality of human resources to support inclusive and sustainable economic growth.